2014
DOI: 10.1118/1.4875978
|View full text |Cite
|
Sign up to set email alerts
|

Improved image quality of cone beam CT scans for radiotherapy image guidance using fiber-interspaced antiscatter grid

Abstract: The evaluated fiber-interspaced grid improved the image quality of the CBCT system for broad range of imaging conditions. Clinical scans show significant improvement in soft tissue visibility and uniformity without the need to increase the imaging dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 23 publications
0
41
1
Order By: Relevance
“…Many methods have been proposed to cope with the shortcomings of CBCT, including antiscatter grids and software‐based solutions 10–15 . Convolution‐based methods, in which the scatter is modeled as a convolution of the projections, can be found in routine clinical use 16–19 …”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been proposed to cope with the shortcomings of CBCT, including antiscatter grids and software‐based solutions 10–15 . Convolution‐based methods, in which the scatter is modeled as a convolution of the projections, can be found in routine clinical use 16–19 …”
Section: Introductionmentioning
confidence: 99%
“…The fraction ( S f , ranging from 0 to 1), is determined from a phantom experiment using a Catphan 600 (or comparable) image quality phantom. The S f parameter was optimized to obtain maximum uniformity in the reconstructed scan . In the case when no ASG is used, the optimal value of this parameter is 0.24.…”
Section: Methodsmentioning
confidence: 99%
“…In general, studies focusing on software estimation techniques have been mostly evaluated in a binary context, i.e., with or without an ASG, without going in depth regarding the effect a different grid design would have on the image quality improvements. In our previous work, we have found that the ratio of the primary and secondary transmission, i.e., selectivity might play a role in applicability of the anti‐scatter grids to cone beam CT imaging, with a grid of high selectivity (around 12) leading to relevant image quality improvements. Sisniega et al .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of hardware developments are dual-energy CT scanning; time-of-flight PET scanning; combined uses of CT, MR and PET; and refined filters for detectors. 84 As these technologies are refined so is the software following them, and their use will to a larger and larger extent become standard. The field of 4D imaging has been in fast development since 2000 and has changed the field of radiotherapy for lung cancer, as described in this review.…”
Section: Dose Painting and Motionmentioning
confidence: 99%